Management of major defoliators of soybean using microbial agents: Management of major defoliators of soybean using microbial agents - R S JADHAV; S P MEHTRE; V R GHUGE (Journal of Oilseeds Research, 2023)
Field experiment was conducted in kharif 2019-20 at AICRP on Soybean, V.N.M.K.V., Parbhani to evaluate the bioefficacy of different biopesticides along with control against major defoliators of soybean. Among the different treatments, after 2nd spray, at 7 DAT, microbial agent N. rileyi recorded significantly lowest of 0.58 larvae/mrl and found superior over rest of the microbial agents in reducing the population of semiloopers. However, it was found at par with the microbial agent B. bassiana (0.75 larvae/mrl). Next best microbial agents were treatment Bt (0.83 larvae/mrl) and M. anisopliae (1.00 larvae/mrl). The microbial agent treatment N. rileyi recorded highest of 1281 kg/ha yield. However, it was found at par with microbial agents treatment B. bassiana (1141 kg/ha) and Bt (1110 kg/ha).